Logical - Soledad (s.l. Warner, 2017)
1. Logical (Roger Hodgson) 2. Paraphrase (Alexander Gurning) 3. Adagio assai (Maurice Ravel) 4. Querelle (Sergei Prokofiev) 5. Valse-Galop (Sergei Prokofiev) 6. Marejadilla (Astor Piazzolla) 7. Prélude (César Franck) 8. Fugata (Astor Piazzolla) 9. Grace (Jeff Buckley) 10. Préambule (Manu Comté) 11. Des pas sur la neige (Claude Debussy)